Extraocular Muscle Enlargement in Growth Hormone–Secreting Pituitary Adenomas - Coutu, B.; Alvarez, D.A.; Ciurej, A.; Moneymaker, K.; White, M.; Zhang, C.; Drincic, A. (American Journal of Neuroradiology, 2022)
BACKGROUND AND PURPOSE: While Graves disease is the most common cause of extraocular muscle enlargement, case reports have also associated growth hormone-secretory pituitary adenomas with this same phenomenon. We investigated the prevalence and response to treatment of extraocular muscle enlargement in patients with growth hormone-secretory pituitary adenomas.MATERIALS AND METHODS: We retrospectively reviewed extraocular muscle sizes using MR imaging in patients with growth hormone–secretory pituitary adenomas who underwent a transsphenoidal surgical resection compared with a matched control group with nonsecretory pituitary adenomas. Descriptive and comparative statistics were used to evaluate patient characteristics and extraocular muscle sizes between the 2 groups.RESULTS: We identified 16 patients who presented with growth hormone–secreting pituitary adenomas and underwent transsphenoidal surgical resection from 2010 to 2019. The average diameter of the extraocular muscle at the time of diagnosis for the group with growth hormone-secretory pituitary adenomas was larger than that in the control group (4.7 versus 3.8 mm, P < .001). Nine patients achieved insulin-like growth factor 1 level normalization at a median of 11.5 months before their most recent MR imaging evaluation. The average size of the extraocular muscles of patients who achieved a normalized insulin-like growth factor 1 was smaller compared with those that did not (difference, 0.7 mm; 95% CI, 0.3–1.2 mm; P < .001), approaching the size of extraocular muscle in the control group.CONCLUSIONS: We describe a high prevalence of extraocular muscle enlargement in patients with growth hormone–secreting pituitary adenomas. Additionally, we note that the size of extraocular muscles decreased with associated improvement in the biochemical control of acromegaly.EOMextraocular muscleGHgrowth hormoneIGF-1insulin-like growth factor 1TEDthyroid eye diseaseTSStranssphenoidal surgicalULNupper limit of normal